Meroterpenoid Dimers from Ganoderma Mushrooms and Their Biological Activities Against Triple Negative Breast Cancer Cells - Qin, Fu-Ying; Chen, Yan-Yi; Zhang, Jiao-Jiao; Cheng, Yong-Xian (Frontiers in Chemistry, 2022)
(±)-Dimercochlearlactones A−J (1–10), ten pairs of novel meroterpenoid dimers and one known spirocochlealactone A (11) were isolated from the fruiting bodies of Ganoderma mushrooms. Their structures were elucidated on the basis of 1D and 2D NMR and HRESIMS data. The absolute configurations of the enantiomers of dimercochlearlactones A−F (1–6) and dimercochlearlactone H (8) were assigned by electronic circular dichroism (ECD) calculations. Biological evaluation showed that (+)- and (–)-2, (–)-3, and (+)- and (–)-11 are cytotoxic toward human triple negative breast cancer (TNBC) cells (MDA-MB-231) with IC50 values of 28.18, 25.65, 11.16, 8.18, and 13.02 μM, respectively. Wound healing assay revealed that five pairs of meroterpenoids (±)-5−(±)-7 and (±)-10 could significantly inhibit cell mobility at 20 μM in MDA-MB-231 cells. The results provide a new insight into the biological role of Ganoderma meroterpenoids in triple negative breast cancer (TNBC).